2021
DOI: 10.1021/acsaem.1c01445
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Deposition: A Breakthrough Technique for Proton Exchange Membrane Fuel Cell Catalyst Layer Fabrication

Abstract: This Spotlight article presents the state-of-the-art of electrospray deposition technique applied to the fabrication of proton exchange membrane fuel cell (PEMFC) components, mainly focusing on catalyst layers in gas diffusion electrodes. The atomization of a suspension of particles over a substrate under the influence of a strong electric field results in the growth of a film with macroporous morphology and many interesting properties. This so-called electrospray deposition has reported many noteworthy benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Proton-exchange-membrane fuel cells offer a promising replacement for traditional combustion engines that have deleterious emissions. The catalyst layers of these cells are currently produced via ink fabrication and deposition involving empirically formulated colloidal dispersions of the perfluorinated sulfonic acid polymer (PFSA) and other ionomers. Colloidal dispersions are commonly assumed to be stable when the total interparticle potential-energy maximum is more than a few k B T units, where k B is Boltzmann’s constant and T is absolute temperature. When the potential-energy maximum is less than this value or is negative everywhere, the dispersion is unstable and particles aggregate. ,,, Aggregation kinetics in a quiescent dispersion often follows perikinetic Smoluchowski kinetics that depend strongly on the pairwise interaction energies between particles. ,,, For electrostatically stabilized charged particle dispersions in electrolyte-supporting solvents, the pairwise interaction potential traditionally consists of a Hamaker attractive interaction and a repulsive electrostatic interaction (i.e., so-called DLVO theory). The electrostatic pair potential originates from the overlap of diffuse double layers encompassing two charged interacting particles. When the opposing particles separate significantly beyond the Debye length, the intervening solution is electrically neutral.…”
Section: Introductionmentioning
confidence: 99%
“…Proton-exchange-membrane fuel cells offer a promising replacement for traditional combustion engines that have deleterious emissions. The catalyst layers of these cells are currently produced via ink fabrication and deposition involving empirically formulated colloidal dispersions of the perfluorinated sulfonic acid polymer (PFSA) and other ionomers. Colloidal dispersions are commonly assumed to be stable when the total interparticle potential-energy maximum is more than a few k B T units, where k B is Boltzmann’s constant and T is absolute temperature. When the potential-energy maximum is less than this value or is negative everywhere, the dispersion is unstable and particles aggregate. ,,, Aggregation kinetics in a quiescent dispersion often follows perikinetic Smoluchowski kinetics that depend strongly on the pairwise interaction energies between particles. ,,, For electrostatically stabilized charged particle dispersions in electrolyte-supporting solvents, the pairwise interaction potential traditionally consists of a Hamaker attractive interaction and a repulsive electrostatic interaction (i.e., so-called DLVO theory). The electrostatic pair potential originates from the overlap of diffuse double layers encompassing two charged interacting particles. When the opposing particles separate significantly beyond the Debye length, the intervening solution is electrically neutral.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of being transported to the substrate, the solution forms a spray plume. The solvent fully (or partially) evaporates, and the droplet size decreases until reaching the Rayleigh limit, creating a thin film of PEDOT:PSS on the substrate . During ESD deposition, two factors are most critical: (i) achieving uniform PEDOT:PSS droplets by exploiting the electrospray mode of deposition and (ii) deposition of hydrophilic PEDOT:PSS thin films on the carbon yarn substrates by controlling the wettability of PEDOT:PSS droplets.…”
Section: Resultsmentioning
confidence: 99%
“…The solvent fully (or partially) evaporates, and the droplet size decreases until reaching the Rayleigh limit, creating a thin film of PEDOT:PSS on the substrate. 47 During ESD deposition, two factors are most critical: (i) achieving uniform PEDOT:PSS droplets by exploiting the electrospray mode of deposition and (ii) deposition of hydrophilic PEDOT:PSS thin films on the carbon yarn substrates by controlling the wettability of PEDOT:PSS droplets. Various techniques can be employed to reduce the surface tension of the PEDOT:PSS solution such as adding a surfactant to the spray solution or mixing secondary solvents with lower surface tension.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most effective strategies for reducing Pt use in the cathode is to increase the three-phase boundary by modulating the interface structure between the polymer electrolyte membrane (PEM) and catalyst layer (CL). It has been also reported that in the CL with a thickness of several micrometers in general, catalysts located far from the membrane surface exhibit low ORR performance . Accordingly, to improve the PEMFCs’ performance and to reduce Pt usage, it is required to place Pt particles in closer proximity to the membrane by roughening the membrane surface.…”
Section: Introductionmentioning
confidence: 99%